2002
DOI: 10.1385/bter:89:1:1
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Tissue Trace Elements in Patients with Breast Cancer in Taiwan

Abstract: The objective of this study was to compare levels of four elements (zinc, copper, selenium, and iron) in the serum and tissue of 68 breast tumor patients (benign and malignant), from a teaching hospital in central Taiwan. Samples of normal tissue (5 cm away from tumor) were also taken from patients with malignant tumors. Only serum was taken from the 25 healthy persons in the control group. Results showed that Zn, Cu, Se, Fe, Cu/Zn, Cu/Se, and Cu/Fe were present in different amounts in the serum of each of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
174
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(184 citation statements)
references
References 11 publications
8
174
0
2
Order By: Relevance
“…It is notable that Se concentration in the neoplastic tissue was nearly fourfold greater than in the adjacent normal breast tissue. Our findings regarding serum/tissue Se levels in patients suffering from breast cancer are in agreement with other reports in patients with lung, gastric, renal, colorectal and breast cancer, where an increased concentration of Se in the neoplastic tissue was found (Garg et al, 1994;Sharma et al, 1994;Burguera et al, 1995;Kuo et al, 2002;Charalabopoulos et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It is notable that Se concentration in the neoplastic tissue was nearly fourfold greater than in the adjacent normal breast tissue. Our findings regarding serum/tissue Se levels in patients suffering from breast cancer are in agreement with other reports in patients with lung, gastric, renal, colorectal and breast cancer, where an increased concentration of Se in the neoplastic tissue was found (Garg et al, 1994;Sharma et al, 1994;Burguera et al, 1995;Kuo et al, 2002;Charalabopoulos et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…To our best knowledge, the present study is the fourth one in the last 40 years (Pub-Med search) providing information regarding the neoplastic tissue Se concentration in breast cancer patients and the first one providing data for serum/tissue Se concentrations simultaneously, in association with serum CEA levels (Garg et al, 1994;Sharma et al, 1994;Kuo et al, 2002). It is notable that Se concentration in the neoplastic tissue was nearly fourfold greater than in the adjacent normal breast tissue.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Studies have shown that copper levels are altered in tumour-bearing mice and humans [11,12], which led to an extensive investigation into the role of copper in carcinogenesis. Various cancers such as breast [13,14], colon [15], prostate [15,16], lung [17] and brain [18] have since been reported to display increased serum and tissue levels of copper. A critical role for copper in angiogenesis was discovered in 1980 [19], and it was later shown that copper induces transcription of VEGF mRNA and protein expression [20,21], contributing to the growth, invasion and metastasis of tumour cells [22,23].…”
mentioning
confidence: 99%